Balancing Energy Consumption, Economic Growth, and Emission Reduction in ASEAN Nations: Insights into the Green Energy Transition - Recto, King Harold A (Archīum Ateneo, 2023)
As the global pandemic recedes, economic activities around the world are resuming. However, this action has also impacted various facets of the society, particularly energy use, economic expansion, and pollution control. While numerous studies have investigated this issue, they have predominantly focused on the global level, with an emphasis on industrialized nations. Naturally, this backdrop is much different from Southeast Asia. In this study, the mathematical relationships between energy consumption, economic growth, and emission reduction were determined using regression modelling of the World Energy Council (WEC) trilemma scores of the Association of Southeast Asian Nations (ASEAN) members, as well as its implications for sustainable energy policy in the ASEAN. The analysis discovered that the best fit model to utilize for this purpose is Gaussian Process Regression - Exponential GPR. In light of the results, measures that would help ASEAN take the Green Energy Transition were proposed: Promoting investments in clean and renewable energy sources to support long-term economic growth and at the same time lower carbon emissions. Encouraging governmental organizations and businesses to adopt and incorporate cleaner energy technology and practices in order to support the goals of global sustainability. Implementing efficient strategies to reduce carbon dioxide emissions resulting from energy use to ensure a trajectory towards greater environmental awareness. Examining variations in energy use and efficiency between the ASEAN region to allow energy policies to be tailored to meet particular demands and difficulties. Motivating people, organizations, and communities to adopt energy-saving practices and technologies in order to collectively reduce energy demand and aid in environmental preservation.